BACTERIOLOGICAL PROFILE AND ANTIBIOTIC SENSITIVITY PATTERN OF HOSPITALACQUIRED SEPTICEMIA IN A TERTIARY CARE HOSPITAL IN NORTH EAST INDIA - Mohanty, Aroop; Singh T, Shantikumar; Kabi, Ankita; Gupta, Pratima; Gupta, Priyanka; Kumar, Pradeep (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of this study was to determine the bacterial agents responsible for hospital acquired septicaemia and to determine the antibiotic sensitivity profile of the bacterial isolates. Methods: Â Three hundred fifty hospitalized clinically suspect septicaemia cases were included in this cross sectional observational study during a period of one year. Blood samples were collected with aseptic precautions for culture following universal precautions. Anti-microbial susceptibility test of the bacterial isolates was performed according to Clinical and Laboratory Standards Institute (CLSI, USA) guidelines.Â Â Â Â Results: Over two-thirds of cultures showed gram positive organism. The most frequently identified Gram positive bacteria were coagulase negative staphylococci and Staphylococcus aureus. Among gram negative bacteria Escherichia coli, Klebsiella spp and Salmonella typhi were isolated. In our study, coagulase negative staphylococci showed maximum resistance to penicillin and erythromycin. Enterobactereciae had maximum sensitivity to carbapenems, tigecycline and aminoglycosides. Conclusion: Gram positive pathogens predominated in the blood stream infections. Résistance to fluoroquinolones, especially in Gram negative bacteria was significantly high. Therefore, rapid microbiological diagnosis and the determinants of antimicrobial susceptibility become relevant for early initiation of antimicrobial therapy.Â Â Â Â